A pilgrim of historiography: Byron and the discourses of history in early nineteenth-century Britain - Pregnolato, Ivan (2016)
This thesis aims to understand Byron’s œuvre in relation to the discourses of history in early nineteenth-century Britain. As a contribution to the historicist critical approaches of the past decades, my dissertation discusses the different ideas surrounding the concept of ‘history’ in the first two decades of the 1800s, a period marked by change. As shown, these discourses of history were notorious for their heterogeneity and, by analysing Byron’s poetry and letters, it becomes evident that Byron engaged with these multiple interpretations as well. Roughly, three types of discourses of history are discussed below: the classical knowledge which was perpetuated in the educational system of the time and discussed in travelogues; the whig interpretation of history and the teleological concept of ‘liberty’ through time; and the idea of powerful forces that act ‘behind’ history, such as economics and the inseparability of power embedded in creating historical narratives. This thesis concludes that is impossible to speak of a single Byronic historical narrative and, rather, argues that Byron’s texts espouse pluralistic conceptualisations of history.